2021
DOI: 10.48550/arxiv.2101.07243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gauge Invariant Autoregressive Neural Networks for Quantum Lattice Models

Abstract: Gauge invariance plays a crucial role in quantum mechanics from condensed matter physics to high energy physics. We develop an approach to constructing gauge invariant autoregressive neural networks for quantum lattice models. These networks can be efficiently sampled and explicitly obey gauge symmetries. We variationally optimize our gauge invariant autoregressive neural networks for ground states as well as real-time dynamics for a variety of models. We exactly represent the ground and excited states of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Finally, we note that several other papers have studied the importance of using equivariant models applied to different symmetry groups. Luo et al [14] show that gauge equivarant neural networks improve performance on gauge invariant Hamiltonians [13], and Pfau et al [40] use a permutation equivariant model to account for identical electrons. Since many important physics models have substantial symmetry, applications of equivariant models are likely to be important for machine-learning methods in computational physics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that several other papers have studied the importance of using equivariant models applied to different symmetry groups. Luo et al [14] show that gauge equivarant neural networks improve performance on gauge invariant Hamiltonians [13], and Pfau et al [40] use a permutation equivariant model to account for identical electrons. Since many important physics models have substantial symmetry, applications of equivariant models are likely to be important for machine-learning methods in computational physics.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially useful on lattice problems which have highly symmetric low-lying energy levels. Recent research [7,[11][12][13][14][15] has shown that forcing neural networks to have the correct symmetry tremendously improves their ability to model the ground state and low-lying excited states of quantum many-body systems.…”
Section: Introductionmentioning
confidence: 99%
“…There have been recent successes in enforcing physical symmetries in the architecture of the models themselves. In quantum many-body physics, recent work has shown that the symmetries of quantum energy levels on lattices can be enforced with gauge equivariant and invariant neural networks [15,9,77,51,67,52]. There is significant work on imposing permutation symmetry in jet assignment for high-energy particle collider experiments with self-attention networks [24,46].…”
Section: Universal Approximation Via Linear Invariant Layers and Irre...mentioning
confidence: 99%
“…Preservation of gauge symmetries is essential for physical interpretations of the resulting variational state. Recent success in designing symmetry-invariant or equivariant neural states [23,[25][26][27][28][29] has shed light on this difficult task. Research for equivariant variational states with non-Abelian symmetries, or even supersymmetries, however, is still incomplete.…”
Section: Related Workmentioning
confidence: 99%